ROLE OF KSHARASUTRA IN THE MANAGEMENT OF RECURRENT EAR PINNA KELOID - A CASE STUDY - Mandavkar (Pandhare), Kalpana Chandrakant; Pandhare, Sachin; K. Jadhav, Dnyaneshwar. (International Journal of Ayurveda and Pharma Research, 2015)
Ear pinna Keloid is an over growth of the fibrous tissue which is concerned in wound healing and strengthening of the wound. The cause of keloid is piercing, pimple, acne, chickenpox, insect bite, infection, repeated trauma. As per ear pinna keloid excessive and repeated ear piercing is main cause which is bad gift of modern style.Keloids affect both sexes equally, although the incidence in young female patients has been higher than in young males, probably reflecting the greater frequency of ear lobe piercing among women. The frequency of occurrence is 15 times higher in highly pigmented people.Surgery is one of the treatments on that. But its not last and best. because even after surgery there is chances of recurrence. The most effective treatment is superficial external beam radiotherapy (SRT), but its economically costly. So comparative to all this Ksharasutra is cheap and best result with minimum injury.In Ayurvedic samhita its described as Arbuda of Karna Pali. Ksharasutra is best treatment as compare with modern surgery. Ksharasutra do duel work excision as well as healing. It is have property of incision, excision, debridement, scrapping along with aerostatic, antiseptic and healing. Present case is successful management of recurrent ear pinna keloid by Ksharasutra.